1996
DOI: 10.1021/bi9607259
|View full text |Cite
|
Sign up to set email alerts
|

Minor-Groove Recognition of Double-Stranded RNA by the Double-Stranded RNA-Binding Domain from the RNA-Activated Protein Kinase PKR

Abstract: The human double-stranded RNA- (dsRNA) activated protein kinase (PKR) has a dsRNA-binding domain (dsRBD) that contains two tandem copies of the dsRNA-binding motif (dsRBM). The minimal-length polypeptide required to bind dsRNA contains both dsRBMs, as determined by mobility-shift and filter-binding assays. Mobility-shift experiments indicate binding requires a minimum of 16 base pairs of dsRNA, while a minimal-length site for saturation of longer RNAs is 11 base pairs. Bulge defects in the helix disfavor bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
318
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(344 citation statements)
references
References 81 publications
22
318
4
Order By: Relevance
“…The importance of specific 29-hydroxyl groups of an RNA in the interaction with proteins has been investigated for RNA binding to a phage coat protein (Baidya & Uhlenbeck, 1995), for a human double-stranded RNA-binding protein (Bevilacqua & Cech, 1996), for the function of the yeast spliceosome , and HIV regulatory proteins (Iwai et al+, 1992), as well as for recognition of tRNA by aminoacyl-tRNA synthetases+ The first example for the latter was the synthesis of Escherichia coli tRNA Phe and tRNA Lys completely consisting of deoxynucleotides, except for the 39-terminal adenosine (Khan & Roe, 1988)+ These tDNAs required pH 5+5 and the presence of 20% DMSO to restore the acceptor function+ Poor activity was also reported for the deoxy equivalent of E. coli tRNA fMet which was chargeable to 3% compared to the native tRNA (Perreault et al+, 1989)+ RNA-DNA heteroduplexes corresponding to the acceptor stem of tRNA minihelices of E. coli tRNA Ala were also tested for aminoacylation (Musier-Forsyth et al+, 1991)+ The 39-RNA/59-DNA heteroduplex was aminoacylated, but not the 39-DNA/59-RNA heteroduplex+ Studies with oligonucleotide duplexes with single 29-deoxy substitutions, corresponding to the tRNA acceptor stem, identified hydroxyls at G4, U70, C71, and C75 as essential for efficient charging (Musier-Forsyth & Schimmel, 1992)+ The importance of 29-OH groups for the aminoacylation of E. coli tRNA Pro has been investigated with chemically synthesized 59 or 39 oligonucleotides of up to 18 nt in length that were annealed to the corresponding 39-or 59-3/4 tRNA fragment (Liu & Musier-Forsyth, 1994;Yap & Musier-Forsyth, 1995)+ The majority of the single de-oxynucleotide substitutions had only a minor effect on aminoacylation, except U8 which was reduced 22-fold+ These studies indicated that single deoxy substitutions had in most cases only small effects+ Multiple substitutions, however, showed more dramatic effects+ In a recent report yeast tRNA Asp transcripts were enzymatically prepared in which any one of the four nucleotides was replaced by its 29-deoxy derivative (Aphasizhev et al+, 1997)+ Those transcripts containing deoxyuridines or deoxyguanosines were not chargeable+…”
Section: Introductionmentioning
confidence: 99%
“…The importance of specific 29-hydroxyl groups of an RNA in the interaction with proteins has been investigated for RNA binding to a phage coat protein (Baidya & Uhlenbeck, 1995), for a human double-stranded RNA-binding protein (Bevilacqua & Cech, 1996), for the function of the yeast spliceosome , and HIV regulatory proteins (Iwai et al+, 1992), as well as for recognition of tRNA by aminoacyl-tRNA synthetases+ The first example for the latter was the synthesis of Escherichia coli tRNA Phe and tRNA Lys completely consisting of deoxynucleotides, except for the 39-terminal adenosine (Khan & Roe, 1988)+ These tDNAs required pH 5+5 and the presence of 20% DMSO to restore the acceptor function+ Poor activity was also reported for the deoxy equivalent of E. coli tRNA fMet which was chargeable to 3% compared to the native tRNA (Perreault et al+, 1989)+ RNA-DNA heteroduplexes corresponding to the acceptor stem of tRNA minihelices of E. coli tRNA Ala were also tested for aminoacylation (Musier-Forsyth et al+, 1991)+ The 39-RNA/59-DNA heteroduplex was aminoacylated, but not the 39-DNA/59-RNA heteroduplex+ Studies with oligonucleotide duplexes with single 29-deoxy substitutions, corresponding to the tRNA acceptor stem, identified hydroxyls at G4, U70, C71, and C75 as essential for efficient charging (Musier-Forsyth & Schimmel, 1992)+ The importance of 29-OH groups for the aminoacylation of E. coli tRNA Pro has been investigated with chemically synthesized 59 or 39 oligonucleotides of up to 18 nt in length that were annealed to the corresponding 39-or 59-3/4 tRNA fragment (Liu & Musier-Forsyth, 1994;Yap & Musier-Forsyth, 1995)+ The majority of the single de-oxynucleotide substitutions had only a minor effect on aminoacylation, except U8 which was reduced 22-fold+ These studies indicated that single deoxy substitutions had in most cases only small effects+ Multiple substitutions, however, showed more dramatic effects+ In a recent report yeast tRNA Asp transcripts were enzymatically prepared in which any one of the four nucleotides was replaced by its 29-deoxy derivative (Aphasizhev et al+, 1997)+ Those transcripts containing deoxyuridines or deoxyguanosines were not chargeable+…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the 2-5A synthetase family does not contain characteristic dsRBMs (14). For example, the binding of TAR to PKR involves interaction of the minor groove of the doublestranded helix with a dsRNA binding motif (dsRBM) (15). However, this motif is not present in any of the known 2-5A synthetase sequences, and no other structural similarity has been found between PKR and 2-5A synthetase.…”
mentioning
confidence: 99%
“…They also failed to rule out the possibility that antisense oligonucleotides to kip1 and cip1 induce the survival of WEHI-231 cells by their nonspecific effects as oligonucleotides, such as activation of TLR-9, transmitting a survival signal, 28 and of dsRNA-activated kinase. 29 Recently, Banerji et al 30 demonstrated that expression of p27 kip1 induces both cell cycle arrest and apoptosis in WEHI-231 cells. This observation indicates that p27 kip1 can induce apoptosis, but does not show whether BCR-mediated apoptosis requires p27 kip1 and/or cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%